Effect of Turbocharger Compression Ratio on Performance of the Spark-Ignition Internal Combustion Engine - Saad S. Alrwashdeh; Ala’a M. Al-falahat; Talib K. Murtadha (Ital Publication, 2022)
Internal Combustion Engines (ICE) are one of the most important engineering applications that operate based on the conversion of chemical energy from fuel into thermal energy as a result of direct combustion. The obtained thermal energy is then turned into kinetic energy to derive various means of transportation, such as marine, air, and land vehicles. The efficiency of ICE today is considered in the range of the intermediate level, and various improvements are being made to enhance its efficiency. The turbocharger can support the ICE, which works by increasing the pressure in the engine to enhance its efficiency. In this investigation, the effect of the turbocharger pressure on ICE performance was studied in the range of 2 to 10 bar. It was found that the increase in turbocharger pressure enhanced the pressure inside the engine, positively affecting engine efficiency indicators. Therefore, the increase in turbocharger pressure is directly proportional to the ICE efficiency. Doi: 10.28991/ESJ-2022-06-03-04 Full Text: PDF